Evolution and Description of Brand Personality Models in Latin America - Araya-Castillo, L; Mateluna-Sanchez, C; Escobar-Farfan, M (UNIV AUTONOMA CARIBE-UAC, 2016)
The concept of brand personality has been developed strongly the last two decades, generating high interest among researchers and entrepreneurs, as the personality gives a product or service aspects of identifying and differentiating among their peers. From the point of view of consumers, they are who give a unique value to a brand, interaction which could predict the intention of purchase or acquisition of their products and services. Brand personality refers to human personality traits that consumers assign to a brand. Jennifer Aaker (1997) proposes a measurement scale, valid, reliable and generalizable, which identifies five dimensions of personality in existing brands in the United States; competition, emotionality, rudeness, sincerity and sophistication. The model explains that all brands have personality traits which are identifiable by consumers. However, there are new researches that criticize Aaker s model, stating that it cannot be replicated in the context of any industry neither in different cultures, because perceptions and preferences of consumers vary. For this reason, different researchers have raised new proposals of brand personality models, where Latin America is a niche where several authors have presented new measurement scales. In this context, this research aims to conduct a theoretical and evolutionary review of brand personality models that have been used in Latin America, conceptualizing the concepts of brand and personality, in order to characterize the various proposals. In conclusion, Aaker s model is present in most of the analysed studies, confirming the literature support of the five dimensions of brand personality.
Keywords: Brand; model of brand personality; dimensions; personality traits; Latin America